KARAKTERISTIK PERFORMA KUALITATIF DAN KUANTITATIF SAPI PO DAN SAPI LIMPO JANTAN DI KECAMATAN TERBANGGI BESAR KABUPATEN LAMPUNG TENGAH PROVINSI LAMPUNG - Ridho, Salamun; Sulastri, Sulastri; Hamdani, M. Dima Iqbal (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2017)
This research was conducted from August up to October 2016 to compare the qualitative and quantitative performance of 150 heads male Ongole grade cattle and 150 heads male Limousin crossbreed at Terbanggi Besar subdistrict, Lampung Tengah regency, Lampung Province. Survey method were used in this study and purposive sampling were used to determine sample observed. The variables observed were qualitative characters (skin colour, hump, and horn), body measurements (body length (BL), shoulder height (SH), chest circumference (CC)) and body weight (BW). The result of this research indicated that skin colour all of PO cattle observed were white, had jowl, hump, and horn. Skin colour of Limpo cattle were light brown (60%), and dark brown (40%). All of PO cattle observed (100 %) had jowl, 8.6 % of them had hump, 36% of them had horn, and no horns 64%. The quantitative characters of PO cattle ( BL 108.73±5.56 cm, SH 108.28 ± 10.60 cm, CC 137.19 ± 5.77 cm, and BW 238.11 ± 24.40 kg) was lower than that of Limpo cattle(BL 112.56 ± 4.56 cm, SH 120.06 ± 4.94 cm,CC 149.63 ± 7.77cm, and BW 289.93 ± 42.22 kg). The conclusion of this research is the qualitative and quantitative performance of Ongole grade cattle and male Limousin crossbreed there is difference significantly different (P <0,01), in Limpo cattle is higher than PO. Keywords: Limpo cattle, Ongole grade cattle, Qualitative character, and Quantitative character.